Bimetal composites for photocatalytic reduction of CO2 to CO in the near-infrared region by the SPR effect. Issue 16 (19th February 2020) - Jiang, Hua; Gong, Shuaiqi; Xu, Shu; Shi, Penghui; Fan, Jinchen; Cecen, Volkan; Xu, QunJie; Min, YuLin
Abstract : A major challenge in the field of photocatalytic carbon dioxide (CO2 ) reduction is to design catalyst systems featuring high selectivity for CO production, long-term stability and a composition of Earth-abundant elements. Abstract : A major challenge in the field of photocatalytic carbon dioxide (CO2 ) reduction is to design catalyst systems featuring high selectivity for CO production, long-term stability and a composition of Earth-abundant elements. Here, we present a metal–organic framework (MOF) based catalyst to mitigate the technical problems associated with the above-mentioned features. We report a carbon-coated CuNi alloy nanocatalyst obtained by high temperature vacuum treatment of a MOF material (CuNiBTC). The resulting carbon encapsulated CuNi (denoted as CuNi/C) nanoparticles possess a well-designed core–shell composite structure with graphene shells. Meanwhile, we investigated the reaction mechanism of CO2 on the surface of the CuNi/C photocatalyst in an aqueous solution containing triethanolamine. The experimental results show that the activity and catalytic yield of CuNi/C are much higher than those of Cu/C and Ni/C alone. At the same time, the catalytic activity of CuNi/C is also affected by changing the reaction temperature in the preparation process. As a result, the CuNi/C samples can achieve nearly 90% selectivity for NIR-light-driven CO2 reduction to CO. Our approach demonstrates the potential of non-semiconductor materials as catalysts for efficient and selective reduction of CO2 to CO.